2016
DOI: 10.1007/s00403-016-1662-7
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory functions in patients with psoriasis vulgaris: correlations with the severity of the disease

Abstract: It is well known that psoriasis is not only limited to skin, but a systemic autoimmune disease with various comorbidities. Olfactory dysfunction, one of as a common but lesser known symptom of patients with autoimmune diseases, often presents with smell loss. The aim of this study was to assess the olfactory functions in patients with psoriasis and to compare with healthy controls. A total of 50 patients with psoriasis and 43 control subjects were included to the study. The clinical severity of psoriasis was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
12
0
1
Order By: Relevance
“…In the present study 50% of patients with postinfectious olfactory loss showed ANAs. These results suggest that postinfectious smell loss might be related to immune mediated processes as reduced olfactory function has been already shown in several autoimmune meditaed diseases such as multiple sclerosis (27) , pemphigus vulgaris (10) , psoriasis vulgaris (11) and Sjögren syndrome (12) .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In the present study 50% of patients with postinfectious olfactory loss showed ANAs. These results suggest that postinfectious smell loss might be related to immune mediated processes as reduced olfactory function has been already shown in several autoimmune meditaed diseases such as multiple sclerosis (27) , pemphigus vulgaris (10) , psoriasis vulgaris (11) and Sjögren syndrome (12) .…”
Section: Discussionsupporting
confidence: 58%
“…In several autoimmune diseases (8) decreased olfactory function has been shown, e.g. systemic lupus erythematosus (9) , pemphigus vulgaris (10) , psoriasis vulgaris (11) , Sjögren syndrome (12) and Wegener's disease (13,14) . In addition, reduced olfactory function has been shown in several other diseases, which are discussed to be mediated by autoimmune processes, e.g.…”
Section: Neurological Disorders and Autoimmune Processes Have Beenmentioning
confidence: 99%
“…(Ahn et al, 2016). In addition, Aydın et al (2016) found that the olfactory function of patients with psoriasis was significantly worse than that of healthy controls (P < 0.001). These results suggest that m 6 A methylation may be involved in the mechanism of anosmia in psoriasis vulgaris.…”
Section: Discussionmentioning
confidence: 96%
“…Olfactory receptors are known to be expressed not only in nasal tissue but also in skin tissue and specifically in keratinocytes, dendritic cells, and melanocytes ( Ahn et al, 2016 ). In addition, Aydın et al (2016) found that the olfactory function of patients with psoriasis was significantly worse than that of healthy controls ( P < 0.001). These results suggest that m 6 A methylation may be involved in the mechanism of anosmia in psoriasis vulgaris.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation